Diseño y modelado del sistema de puesta a tierra y apantallamiento para la Estación Cotopaxi del Instituto Geográfico Militar. - Abril Chafla, Leonardo Manuel (2021)
The Cotopaxi Station was built by the National Aeronautics and Space Administration (NASA), coming into operation in 1954, it was intended to control the satellites remotely from Ecuador, currently belongs to the Geographic Institute Military (IGM) and its activity is to obtain satellite data, to keep its systems operating, it has an Electric Power System which is made up of an internal distribution yard that has step-down transformers such as elevators that operate with the following voltage levels 22.8 kV, 4.16 kV and 0.22 kV, which generally feed the Atlanta Georgia main antenna and the control station. In this project, the design and modeling of the grounding and shielding system for the Cotopaxi Station is carried out. In the first instance, the diagnosis of the Existing SPT applying the curve intersection and slope methods, then based on the results of the field evaluation it was necessary to carry out a new grounding mesh design, for this purpose a fault current study was carried out in the system and the soil was modeled using the graphical method of Sunde, Box-Cox and mathematical method using the data obtained in a previous measurement of the resistivity of the ground, for the mesh design procedure a graphical interface was created in Matlab. Finally, the proposed design is modeled in the ETAP software using the methodology proposed by IEEE and Finite Elements to validate the final result and indicate that the values obtained are within the national and international regulations. On the other hand, the shielding of the facilities is evaluated according to the risk defined by IEC-62305, which marks important factors among which are the isoceraunic level and the area of the building, using this methodology protection levels were assigned to each building and is the starting point for the application of the electrogeometric model based on rolling spheres to finally locate collector points and Generate a protection area against atmospheric discharges, using AutoCAD software.